EXPLORATION OF MATHEMATICAL ABSTRACT LEARNING USING TACTILE AND VISUAL 3D MEDIA: STUDENT MATHEMATICAL ABSTRACTION SKILL - Dina Amalya Lapele; Puput Papalia (Jurnal Eduscience)
Purpose-This study aims to explore abstract mathematics learning activities using tactile media and 3D visual media, identify the effect of this learning on students' mathematical abstraction skills, and determine the category of students' mathematical abstraction skills.